2019
DOI: 10.1172/jci123524
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 inhibitor geldanamycin reverts IL-13– and IL-17–induced airway goblet cell metaplasia

Abstract: experiments. AP and CS were responsible for the high-throughput sample preparation and data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 160 publications
5
42
2
Order By: Relevance
“…IL-13 treatment induced an increase in MUC5AC staining, as we expected. Consistent with our prior findings, treatment of HPS90i with IL-13 blocked this significant increase in MUC5AC (13). Moreover, exposure to IL-13 induced phosphorylation of p100 S869.…”
Section: Hsp90 Inhibition Blocks Il-13-induced Phosphorylation Of P10supporting
confidence: 92%
See 3 more Smart Citations
“…IL-13 treatment induced an increase in MUC5AC staining, as we expected. Consistent with our prior findings, treatment of HPS90i with IL-13 blocked this significant increase in MUC5AC (13). Moreover, exposure to IL-13 induced phosphorylation of p100 S869.…”
Section: Hsp90 Inhibition Blocks Il-13-induced Phosphorylation Of P10supporting
confidence: 92%
“…We have previously shown that HSP90 inhibition blocks and partially reverts IL-13-induced goblet cell metaplasia in primary human airway epithelia in vitro (13). HSP90 is known to interact with many client proteins.…”
Section: Hsp90 Inhibition Modulates Phosphorylation Of Several Proteimentioning
confidence: 99%
See 2 more Smart Citations
“…IL-17 is activated after binding to the receptors of target cells and ultimately promotes the release of large amounts of in ammatory cytokines from target cells, which is one of many causes of neuronal death in individuals with depression [47]. In addition, some pathological phenomena induced by IL-17 can be reversed by inhibiting the activity of Hsp90 family proteins [48].…”
Section: Discussionmentioning
confidence: 99%